2021
DOI: 10.1038/s41598-020-80731-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visual outcomes between therapy choices and subtypes of polypoidal choroidal vasculopathy (PCV) in Taiwan: a real-world study

Abstract: Polypoidal choroidal vasculopathy (PCV) is a distinctive type of neovascular age-related macular degeneration prevalent in many Asian countries. However, there is still some controversy in how the subtypes of PCV are classified. This post-hoc study redefined the branching vascular network (BVN) and PCV subtypes through retrospective review of indocyanine green angiography (ICGA) and fluorescein angiography images from two observational studies (RENOWNED/REAL). Of the visual outcomes for each angiographic subty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Therefore, non-pachychoroid patients may be more vulnerable. The effects of combination therapy are well documented, and numerous different combination regimens have been proposed 8 , 14 , 16 21 , 35 . In the EVEREST II study, the PDT combination group showed greater improvement in VA and regression of polypoidal lesions than the IVR monotherapy group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, non-pachychoroid patients may be more vulnerable. The effects of combination therapy are well documented, and numerous different combination regimens have been proposed 8 , 14 , 16 21 , 35 . In the EVEREST II study, the PDT combination group showed greater improvement in VA and regression of polypoidal lesions than the IVR monotherapy group.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, after the initial treatment (i.e., one PDT session plus two monthly IVR injections and three monthly IVA injections, respectively), further administration of drug was performed on a pro re nata basis. Given the National Health Insurance reimbursement plan and the compliance of patients, the overall number of injections was low, and this effect has been observed in almost all real-world treatment studies in Taiwan 21 , 44 . This could have affected the final VA of the cohort to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment with anti-VEGF therapy alone is effective in eliminating the fluid from macular area and improving visual acuity; however, it is less effective against closing the polypoidal lesions [ 15 , 16 , 17 ]. Combination therapy, with various combination protocols, has also been suggested by different research groups [ 10 , 16 , 18 , 19 , 20 , 21 , 22 , 23 ]. Our group has also published the visual prognosis between two different treatment protocols, with similar outcomes.…”
Section: Introductionmentioning
confidence: 99%